2007
DOI: 10.1111/j.1365-2109.2007.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA riboprinting analysis of Tilapia species and their hybrids using restriction fragment length polymorphisms of the small subunit ribosomal DNA

Abstract: Morphometric, meristic and DNA riboprinting analyses of Tilapia species and their hybrids inhabiting the River Nile were examined. Morphometric data showed striking similarities and overlapping among Tilapia species, making it impossible to differentiate these species. Meristic characteristics revealed that Tilapia species could be identified into four major groups (Oreochromis niloticus, O. aureus, Sarotherodon galilaeus and Tilapia zillii). The lateral line scales differed significantly between the four Tila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Because of their low cost and little requirements when compared with other molecular techniques, the methodologies developed in this study provide a quick and precise method for the safe identification of the parental species P. corruscans and P. reticulatum and the hybrids ‘pintachara’ and ‘cachapinta’. Other studies confirm the efficiency and reliability of PCR‐RFLP and multiplex‐PCR techniques in the identification of fish species (Teletchea 2009) and hybrids (Padhi & mandal 1997; El‐serafy, Abdel‐Hameid, Awwad & Azab 2007; Hashimoto et al 2009).…”
Section: Discussionmentioning
confidence: 60%
“…Because of their low cost and little requirements when compared with other molecular techniques, the methodologies developed in this study provide a quick and precise method for the safe identification of the parental species P. corruscans and P. reticulatum and the hybrids ‘pintachara’ and ‘cachapinta’. Other studies confirm the efficiency and reliability of PCR‐RFLP and multiplex‐PCR techniques in the identification of fish species (Teletchea 2009) and hybrids (Padhi & mandal 1997; El‐serafy, Abdel‐Hameid, Awwad & Azab 2007; Hashimoto et al 2009).…”
Section: Discussionmentioning
confidence: 60%
“…They concluded that decades of introduction and domestication of L. abu has lead to high adaptation to a wide range of geographical locations that are shown in phenotypic variations with respect to the pure strains. El-Serafy et al (2007) reports that hybridization through extensive inbreeding is a possible course of morphological variation. It is an established fact that most cultured African fish species have been genetically polluted (Olufeagba et al 2002), hence, this could have lead to the remarkable phenotypic changes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because of the effects of the environment or hybrids evolving through extensive inbreeding (El-Serafy et al 2007). Although the comparisons of the morphology between reared and wild salmon stocks have already been conducted by a number of authors (Swain et al 1991, von Cramon-Taubadel et al 2005, Solem et al 2006, there is a lack of information on the level of this variation for most tropical fish species.…”
Section: Introductionmentioning
confidence: 94%
“…niloticus (Nile tilapia) brood fish were obtained from Southern Farm Tilapia (Castalia, NC). The species assignment of the brood fish was verified using morphological characteristics (Popma and Masser 1999) and restriction fragment length polymorphism analyses of PCR-amplified 18S ribosomal DNA (El-Serafy et al 2007). The fish were raised at 28°C in 200 L aquaria arranged into a 2,600 L recirculating system.…”
Section: Whole-mount In Situ Hybridizationmentioning
confidence: 99%